Implementasi Terapi Relaksasi Pada Pasien Ulkus Diabetic Dengan Masalah Ansietas Di Ruang Perawatan Bedah RSUD Poso - Yunita, Agil Rahmah; Suharto, Dewi Nurviana; Faisal, T Iskandar; Nilasanti, Ni Made Ridla (Madago Nursing Journal, 2024)
Diabetic ulcers are a common complication of diabetes mellitus and a significant global health issue. This condition is often accompanied by psychological problems, such as anxiety, due to changes in the patient's physical, social, and emotional conditions. Effective anxiety management can improve the quality of life for patients. This study aims to evaluate the effectiveness of relaxation therapy in addressing anxiety in patients with diabetic ulcers This descriptive study used a case study approach involving a 39-year-old patient treated in the surgical ward of RSUD Poso. The interventions included deep breathing relaxation and music therapy, administered twice daily for 15–30 minutes over six days. Anxiety levels were measured using the Zung Self-Rating Anxiety Scale before and after the intervention. The patient's anxiety score decreased from 70 (severe anxiety) to 55 (mild anxiety) following the relaxation therapy. Subjectively, the patient reported Relaxation therapy effectively reduces anxiety in diabetic ulcer patients and can serve as a vital independent nursing intervention. It is recommended that relaxation therapy be integrated into nursing practice standards as a complementary intervention to pharmacological treatments, supporting the psychological recovery of diabetic ulcer patients anxiety patients.